1996
DOI: 10.1088/0953-4075/29/17/019
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of He and Ne 3p states by polarized electrons

Abstract: Integrated Stokes parameters for the transitions in helium (388.9 nm) and neon (640.2 nm) and (626.7 nm) have been measured over the electron energy range from threshold to 300 eV after excitation by polarized electrons. The measured zero values of for both the He 388.9 and Ne 640.2 nm photons are consistent with the LS coupling of the upper states for each transition. Similarly, the measured non-zero values of for the 626.7 nm photons provide clear evidence of the breakdown of LS coupling for the Ne sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 15 publications
6
25
0
Order By: Relevance
“…With the exception of the work of the Münster group on Hg [13], none involved polarized electrons. Furst et al [5,14] made the first measurements using a polarized electron beam in the study of the heavy noble gases, and the Perth group has recently reported extensive measurements with neon using polarized electrons as well [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the work of the Münster group on Hg [13], none involved polarized electrons. Furst et al [5,14] made the first measurements using a polarized electron beam in the study of the heavy noble gases, and the Perth group has recently reported extensive measurements with neon using polarized electrons as well [7][8][9].…”
mentioning
confidence: 99%
“…While they both have their excited-electron orbital angular momentum, their excitedelectron spins, and j c "lined up" to give the maximal J for the state, the 3 D 3 state has an alignable ( j c 3͞2) core while the 3 P 2 state does not ( j c 1͞2). The tendency of the atomic 3 D 3 alignment to remain high well above threshold has thus in the past been interpreted in terms of an alignment "flywheel" model [7,20]: the "storage" of alignment in the 3 D 3 core could reduce both the depolarizing influence of negative-ion decay and the ordinary fall of P 1 from its threshold value as sublevels with M L . 0 begin to be excited.…”
mentioning
confidence: 99%
“…It is found that the electron polarization is not critically dependent on the conditions of the crystal surface and is very stable over long operating times. 4 For this source, as the emission per unit laser power decreases from 10 to 0.2 A/mW, the change in the measured absolute polarization is less than 0.5%, which is within the error of the polarization measurement technique. This is a surprising result and suggests that contaminants of the surface have little effect on the spin polarization for this surface orientation and for our operating procedures.…”
Section: Electron Polarizationmentioning
confidence: 55%
“…2 The spin polarized electron beam apparatus described here is a significant improvement of our earlier source 3 and has been used for the excitation of neutral helium and neon atoms with observations of spin orbit coupling and electron exchange phenomena. 4,5 The general principle and characteristics of the source, based on photoemission from a GaAs crystal, have been investigated in detail previously. [6][7][8] The significant improvements reported here have resulted in a high electron flux which is shown to be stable over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of integrated Stokes parameters is an established method [11] based on observation of the polarization characteristics of photons emitted after the excitation of atoms by spin polarized electrons. Both types of measurements are based on crossed electron and atomic beams and the use of spin polarized electrons.…”
Section: Experimental Methods -Integrated Stokes Parametersmentioning
confidence: 99%